The China questions : critical insights into a rising power - Rudolph, Jennifer M.; Szonyi, Michael (Cambridge, Massachusetts : Harvard University Press, 2018)
Many books offer information about China, but few make sense of what is truly at stake. The questions addressed in this unique volume provide a window onto the challenges China faces today and the uncertainties its meteoric ascent on the global horizon has provoked. In only a few decades, the most populous country on Earth has moved from relative isolation to center stage. Thirty of the world's leading China experts--all affiliates of the renowned Fairbank Center for Chinese Studies at Harvard University--answer key questions about where this new superpower is headed and what makes its people and their leaders tick. They distill a lifetime of cutting-edge scholarship into short, accessible essays about Chinese identity, culture, environment, society, history, or policy.--
I. Politics: Is the Chinese communist regime legitimate? / Elizabeth J. Perry -- Can fighting corruption save the party? / Joseph Fewsmith -- Does Mao still matter? / Roderick MacFarquhar -- What is the source of ethnic tension in China? / Mark Elliott -- What should we know about public opinion in China? / Ya-Wen Lei -- What does longevity mean for leadership in China? / Arunabh Ghosh -- Can the Chinese Communist Party learn from Chinese emperors? / Yuhua Wang -- II. International relations: Will China lead Asia? / Odd Arne Westad -- How strong are China's armed forces? / Andrew S. Erickson -- What does the rise of China mean for the United States? / Robert S. Ross -- Is Chinese exceptionalism undermining China's foreign policy interests? / Alistair Iain Johnston -- (When) will Taiwan reunify with the mainland? / Steven M. Goldstein -- Can China and Japan ever get along? / Ezra F. Vogel -- III. Economy: Can China's high growth continue? / Richard N. Cooper --Is the Chinese economy headed toward a hard landing? / Dwight H. Perkins -- Will urbanization save the Chinese economy or destroy it? / Meg Rithmire -- Is China keeping its promises on trade? / Mark Wu -- How do China's new rich give back? / Tony Saich -- What can China teach us about fighting poverty? / Nara Dillon -- IV. Environment: Can China address air pollution and climate change? / Michael B. McElroy -- Is there environmental awareness in China? / Karen Thornber -- V. Society: Why does the end of the one-child policy matter? / Susan Greenhalgh -- How are China and its middle class handling aging and mental health? / Arthur Kleinman -- How important is religion in China? / James Robson -- Will there be another Dalai Lama? / Leonard W. J. van der Kuijp -- Does law matter in China? / William P. Alford -- Why do so many Chinese students come to the United States? / William C. Kirby -- VI. History and culture: Who is Confucius in today's China? / Michael Puett --Where did the Silk Road come from? / Rowan Flad -- Why do intellectuals matter to Chinese politics? / Peter K. Bol -- Why do classic Chinese novels matter? / Wai-yee Li -- How have Chinese writers imagined China's future? / David Der-wei Wang -- Has Chinese propaganda won hearts and minds? / Jie Li -- Why is it still so hard to talk about the Cultural Revolution? / Xiaofei Tian -- What is the future of China's past? / Stephen Owen -- How has the study of China changed in the last sixty years? / Paul A. Cohen.
"In celebration of the 60th anniversary of the Fairbank Center for Chinese Studies at Harvard University"--Title page verso.
Includes bibliographical references (pages 297-307) and index.
Keywords: ulkopolitiikka -- Kiina; kansainväliset suhteet -- Kiina; sisäpolitiikka -- Kiina; kommunistiset puolueet -- Kiina; talouselämä -- Kiina